2019
DOI: 10.1111/1751-7915.13439
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive, ratiometric determination of intracellular pH in Pseudomonas species using a novel genetically encoded indicator

Abstract: Summary The ability of Pseudomonas species to thrive in all major natural environments (i.e. terrestrial, freshwater and marine) is based on its exceptional capability to adapt to physicochemical changes. Thus, environmental bacteria have to tightly control the maintenance of numerous physiological traits across different conditions. The intracellular pH (pHi) homoeostasis is a particularly important feature, since the pHi influences a large portion of the biochemical processes in the cell. Despite its importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 94 publications
(111 reference statements)
2
27
0
Order By: Relevance
“…However, the pH i of WT and Δ speA strains remained within the physiological pH range ( Figure 4 ). These results conform to reports that bacteria maintain their pH i within a narrow pH range despite exposure and growth under varied extracellular pH conditions [ 51 , 52 ]. Although pneumococci are reported to be tolerant of pH 4.4 [ 51 ] in phagosome vesicles, our results show increased sensitivity of Δ speA to acid stress, suggesting that impaired polyamine synthesis renders pneumococci more susceptible to acid stress.…”
Section: Discussionsupporting
confidence: 92%
“…However, the pH i of WT and Δ speA strains remained within the physiological pH range ( Figure 4 ). These results conform to reports that bacteria maintain their pH i within a narrow pH range despite exposure and growth under varied extracellular pH conditions [ 51 , 52 ]. Although pneumococci are reported to be tolerant of pH 4.4 [ 51 ] in phagosome vesicles, our results show increased sensitivity of Δ speA to acid stress, suggesting that impaired polyamine synthesis renders pneumococci more susceptible to acid stress.…”
Section: Discussionsupporting
confidence: 92%
“…To more directly test the effects of cadaverine, we monitored intracellular pH of wild‐type and Δ paeA strains during cadaverine treatment. We used a green fluorescent protein (GFP) that responds to pH change (Arce‐Rodriguez et al., 2019). We confirmed the response to pH by incubating cells in saline solutions buffered at various pH in the presence of cell‐permeable acids and bases, thereby equilibrating intracellular and extracellular pH.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular pH was first quantified on the single cell level using membrane-permeable pH-dependent fluorescent dyes (Siegumfeldt et al, 2000;Rasmussen et al, 2008;Kurre et al, 2013;Chao et al, 2017). A more recent approach, which obviates the need for a dye loading step and its potential invasive effects (Han and Burgess, 2010), uses genetically encoded fluorescent proteins, such as pH-sensitive derivatives of GFP (Miesenböck et al, 1998;Martinez et al, 2012;Kurre et al, 2013;Morimoto et al, 2016;Rupprecht et al, 2017;Arce-Rodríguez et al, 2019). Aside from excellent temporal (< 1 s) and pH (< 0.1) resolution (Kralj et al, 2011), a fusion between pHluorin and FliG of the BFM has shown local pH measurements with subcellular spatial resolution (Morimoto et al, 2016).…”
Section: Measurements Ofmentioning
confidence: 99%